The cultural processing of 9/11 from a transcultural perspective (KULT_online, 2015)
This romance-studies work focuses on the European reception, in print media from three countries, of American cultural products that deal with September 11, 2001. With a thoroughly established theoretical framework and clearly defined methods, Schmidtgall achieves a unique contribution to the growing interdisciplinary field in the study of culture that investigates 9/11 as a traumatic media event.